2010
DOI: 10.1007/s11605-009-1105-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Metachronous Rectal Cancer Following Ileorectal Anastomosis for Familial Adenomatous Polyposis

Abstract: Effective IRA requires selection of patients without invasive rectal cancer and without dense rectal polyps in whom long-term postoperative follow-up of the residual rectum is possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…Therefore, the 33 % of other reasons as a cause of death does not reflect the morbidity of IRAoperated patients per se: instead it reflects the longer follow-up time. After the year 1991, there was no survival benefit found for IPAA-operated patients, which is an outcome that is in line with a previous study by Yamaguchi and colleagues, who found no survival difference in 96 patients who had either IPAA or IRA [6]. The improvement survival figures for IRA-operated patients during the IPAA era can be interpreted as being due to successful patient selection.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the 33 % of other reasons as a cause of death does not reflect the morbidity of IRAoperated patients per se: instead it reflects the longer follow-up time. After the year 1991, there was no survival benefit found for IPAA-operated patients, which is an outcome that is in line with a previous study by Yamaguchi and colleagues, who found no survival difference in 96 patients who had either IPAA or IRA [6]. The improvement survival figures for IRA-operated patients during the IPAA era can be interpreted as being due to successful patient selection.…”
Section: Discussionsupporting
confidence: 88%
“…Advantages of ileorectal anastomosis emphasized by its advocates are debatable. Functional results and survival rate are nearly the same in patients 5 years after the mentioned procedure and ileal pouch-anal anastomosis [22]. Functioning of patients after restorative proctocolectomy assessed by the SF-36 questionnaire is comparable to that of not operated on [23].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of rectal cancer and secondary proctectomy following rectum sparing surgery in familial adenomatous polyposis (FAP) depends on genotype and colorectal phenotype [1,2]. Following total colectomy with ileorectal anastomosis (TC-IRA), the cumulative risk of developing cancer in the residual rectum has been documented to be in the region of 10%-25% after 15-25 years and increasing to 29%-30% by the age of 60 years [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%